2017
DOI: 10.2174/1381612822666161021142835
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Pharmacology and Toxicology of Steviol Glycosides Extracted from Stevia rebaudiana

Abstract: Stevia rebaudiana Bertoni is a sweet and nutrient-rich plant belonging to the Asteraceae family. Stevia leaves contain steviol glycosides including stevioside, rebaudioside (A to F), steviolbioside, and isosteviol, which are responsible for the plant's sweet taste, and have commercial value all over the world as a sugar substitute in foods, beverages and medicines. Among the various steviol glycosides, stevioside, rebaudioside A and rebaudioside C are the major metabolites and these compounds are on average 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(74 citation statements)
references
References 0 publications
1
67
0
6
Order By: Relevance
“…The metabolized components essentially leave the body and there is no accumulation. Studies have shown that compounds found in stevia are not teratogenic, mutagenic, or carcinogenic and cause no acute or subacute toxicity . Moreover, reports have been promising regarding the potential benefits of stevia against inflammation, carcinogenesis, atherosclerosis glucose control, and hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…The metabolized components essentially leave the body and there is no accumulation. Studies have shown that compounds found in stevia are not teratogenic, mutagenic, or carcinogenic and cause no acute or subacute toxicity . Moreover, reports have been promising regarding the potential benefits of stevia against inflammation, carcinogenesis, atherosclerosis glucose control, and hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only the accumulation of free drugs at the target site can exert their curative effects. Excessive exposure or accumulation in healthy tissues would rather lead to toxic and side effects [51–54]. Acquiring comprehensive knowledge about the pharmacokinetics of modified drugs is vitally important to design more efficient PEGylated pharmaceuticals with good targeting property and have better control of undesired side effects [55–58].…”
Section: Introductionmentioning
confidence: 99%
“…Stevia rebaudiana (Stevia) extract, a natural non-nutritive sweeteners, has drawn increasing attention because, in addition to being a non-cariogenic sweetener [1], it seems to have hypotensive, hypoglycaemic, antidiabetic, anticariogenic, antioxidant, hypotensive, antihypertensive, antimicrobial, anti-inflammatory and anti-tumour activities [2,3]. The sweetening effect of Stevia is due to glycosides of the aglycone steviol (ST), an ent-kaurene-type diterpene (Figure 1, table 1).…”
Section: Introductionmentioning
confidence: 99%